SYMMETRICAL SCAFFOLDING STRATEGY ON STUDENTS’ READING COMPREHENSION ABILITY IN NARRATIVE TEXT - Sri Lestari; Azizah Azizah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
This research consists of two variables, namely the independent variable (Symmetrical Scaffolding Strategy) and the dependent variable (Students’ Reading Comprehension Ability in Narrative Text). The objective of this research is to find out whether or not there is significant effect of Symmetrical Scaffolding Strategy. This research was conducted on grade Eleven Students’ Reading Comprehension Ability in Narrative text at SMA Islam As-Syafi’iyah 02 Bekasi, in the academic year of 2017/2018. Research method applied in this research was quantitative quasi-experimental, and the research design was randomized post-test only control group design. To collect the data, the writer used one instrument in the form of objective test, with number of questions are sixty for reading comprehension ability that have been tried out in grade eleven at SMA Patriot Bekasi. This research consists of two variables, namely the independent variable (Symmetrical Scaffolding Strategy) and the dependent variable (Students’ Reading Comprehension Ability in Narrative Text). The objective of this research is to find out whether or not there is significant effect of Symmetrical Scaffolding Strategy. This research was conducted on grade Eleven Students’ Reading Comprehension Ability in Narrative text at SMA Islam As-Syafi’iyah 02 Bekasi, in the academic year of 2017/2018. Research method applied in this research was quantitative quasi-experimental, and the research design was randomized post-test only control group design. To collect the data, the writer used one instrument in the form of objective test, with number of questions are sixty for reading comprehension ability that have been tried out in grade eleven at SMA Patriot Bekasi. The scores obtained from the try out class were used to analyze the validity, reliability, discrimination power and difficulty index of each question item in the only one instrument. The population of this research was grade eleven students that consist of 147 students were seating in 5 classes. The number of samples was 60 students, 30 students were in control class, and 30 students were in experimental class that taken through cluster random sampling. Symmetrical Scaffolding Strategy employed in experimental class and conventional strategy used in control class, then followed by the post-test in each classes. The analysis using SPSS namely one way anova formula produced Significance (Sig.) value of 0.000, it means that HA (sig. value < 0.05) was accepted and H0 (sig. value > 0.05) was rejected. Finally the research’s result is there is significant effect of Symmetrical Scaffolding Strategy on Grade Eleven Student’s Reading Comprehension Ability in Narrative Text at SMA Islam As-Syafi’yah 02, Bekasi, in the Academic Year of 2017/2018. scrimination power and difficulty index of each question item in the only one instrument. The population of this research was grade eleven students that consist of 147 students were seating in 5 classes. The number of samples was 60 students, 30 students were in control class, and 30 students were in experimental class that taken through cluster random sampling. Symmetrical Scaffolding Strategy employed in experimental class and conventional strategy used in control class, then followed by the post-test in each classes. The analysis using SPSS namely one way anova formula produced Significance (Sig.) value of 0.000, it means that HA (sig. value < 0.05) was accepted and H0 (sig. value > 0.05) was rejected. Finally the research’s result is there is significant effect of Symmetrical Scaffolding Strategy on Grade Eleven Student’s Reading Comprehension Ability in Narrative Text at SMA Islam As-Syafi’yah 02, Bekasi, in the Academic Year of 2017/2018.